The Influence of Word of Mouth and Social Media Marketing on Students' Decision to Choose a University With Brand Image as a Mediating Variable (Case Study at Darunnajah University) - Arief, Zakiyanto; Brabo, Nora Andira (SEAN Institute, 2025)
The increasing competition among higher education institutions requires universities to develop effective marketing strategies to attract prospective students. This study aims to examine the influence of Word of Mouth and Social Media Marketing on students’ decisions to choose a university, with Brand Image serving as a mediating variable. A quantitative survey was conducted with 222 active students at Universitas Darunnajah, and the data were analyzed using Partial Least Squares (PLS) with SmartPLS software. The findings reveal that Word of Mouth significantly affects Brand Image (T-statistic = 2.671, p < 0.05) and student decision-making (T-statistic = 3.512, p < 0.05), while Social Media Marketing also significantly impacts Brand Image (T-statistic = 4.205, p < 0.05) and student decisions (T-statistic = 5.027, p < 0.05). Furthermore, Brand Image significantly mediates the relationship between both communication strategies and student decision-making. This study contributes strategic insights for universities by emphasizing the importance of enhancing brand image through digital engagement and positive interpersonal communication to improve student enrollment outcomes.